Complete mitochondrial genome of the Italian slow-worm Anguis veronensis Pollini, 1818, and its comparison with mitogenomes of other Anguis species. Issue 1 (1st January 2017) - Strzała, Tomasz; Grochowalska, Renata; Najbar, Bartłomiej; Crottini, Angelica; Kosowska, Barbara; Jablonski, Daniel
Abstract: In this paper, we present complete mitochondrial genome of the Italian legless lizard species Anguis veronensis Pollini, 1818. The complete mtDNA consisted of 13 protein-coding genes, 22 tRNAs, and two rRNA genes which in total formed a DNA strand of 17, 322 bp. Anguis veronensis mitogenome had the same gene order as two other compared Anguis spp ., i.e. A. cephallonica and A. fragilis . The base composition of A. veronensis mitochondrial genome was A – 30.8%, T – 24.9%, C – 29.9%, G – 14.4%, with an A + T bias (55.7%). The newly described genome provides valuable data for future comparative mitogenomic analysis within Anguis genus.